The Oxford unicompartmental knee arthroplasty: a radiological perspective. - Mukherjee, K; Pandit, H; Dodd, C; Ostlere, S; Murray, D (2008)
Unicompartmental knee arthroplasty (UKA) is increasingly being performed in both specialist centres as well as district hospitals. The radiologists should be aware of the required preoperative imaging, the normal appearance, and complications of this procedure. Unfortunately, very little is available in the radiology literature. This review aims to provide a radiological perspective to an already widely used procedure.